2010
DOI: 10.1088/0957-4484/21/16/165703
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of physisorption of nucleobases on boron nitride nanotubes: a new class of hybrid nano-biomaterials

Abstract: We investigate the adsorption of the nucleic acid bases-adenine (A), guanine (G), cytosine (C), thymine (T) and uracil (U)-on the outer wall of a high curvature semiconducting single-walled boron nitride nanotube (BNNT) by first-principles density functional theory calculations. The calculated binding energy shows the order: G > A approximately C approximately T approximately U, implying that the interaction strength of the high curvature BNNT with the nucleobases, G being an exception, is nearly the same. A h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
78
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(84 citation statements)
references
References 38 publications
6
78
0
Order By: Relevance
“…However, the poor sensitivity and high temperature operability in metal oxide devices; researchers have been investigating in new alternative materials such as silicene, CNT, MoS 2 etc. for sensing applications [12][13][14][15][16][17] . MoS 2 has been found to have the potential to overcome the material-dependent shortcomings for biosensing applications 8 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the poor sensitivity and high temperature operability in metal oxide devices; researchers have been investigating in new alternative materials such as silicene, CNT, MoS 2 etc. for sensing applications [12][13][14][15][16][17] . MoS 2 has been found to have the potential to overcome the material-dependent shortcomings for biosensing applications 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the isolation of BNNTs with the assistance of peptides has been successfully achieved in experiment29. Moreover, theoretical studies showed that DNA and polynucleotides has strong interactions with BNNTs3031. These studies give a strong hint on the dispersion of BNNT in aqueous with the assistance of DNA or polynucleotides molecules.…”
mentioning
confidence: 99%
“…In recent decades, 0-2D nanostructures based on carbon [1] or boron nitride [2][3][4][5][6] have attracted the attention of experimental and theoretical scientists due to the potential application of these materials in areas such as the transport and delivery of drugs. Moreover, Ciofani et al [7,8] conducted a wide study of the biocompatibility of nanotubes of boron nitride (BNNTs) and their biomedical applications, and the Golberg and Bando group recently reported the transport of a drug that helps decrease cancer using nanosheets of BN with high solubility in water [9].…”
Section: Introductionmentioning
confidence: 99%